1981
DOI: 10.1126/science.214.4516.95
|View full text |Cite
|
Sign up to set email alerts
|

Response : Hydralazine Reactions

Abstract: most of the drug would decompose. Thus decomposition products may be the reactive species in the system described by Dubroff and Reid. This criticism regarding stability has been made about other studies (7). (v) Hydralazine is known to concentrate (400:1, vessel concentration to plasma concentration) in blood vessels of animals after a dose of 14C-labeled hydralazine (7). Immunogenic reactions may be initiated in vessels, or their collagen (7). Collagen is known to have carbonyl groups capable of reacting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Such a reaction also proceeds with hydralazine. We have shown that a large percentage of thymine bases in DNA were modified and excised by hydralazine (16). The extent of the modification and excision was dependent on the concentration and time of exposure to drug.…”
Section: Molecular Models For Hydralazine-related Systemic Lupus Erytmentioning
confidence: 98%
See 3 more Smart Citations
“…Such a reaction also proceeds with hydralazine. We have shown that a large percentage of thymine bases in DNA were modified and excised by hydralazine (16). The extent of the modification and excision was dependent on the concentration and time of exposure to drug.…”
Section: Molecular Models For Hydralazine-related Systemic Lupus Erytmentioning
confidence: 98%
“…We have shown that hydralazine alters the pyrimidine bases of DNA (11,16). Modified DNA can be highly immunogenic (17).…”
Section: Molecular Models For Hydralazine-related Systemic Lupus Erytmentioning
confidence: 98%
See 2 more Smart Citations